But it’s legal, isn’t it? Law and ethics in nursing practice related to medical assistance in dying - Schiller, Catharine J. (Nursing philosophy, 2019)
In June 2015, the Supreme Court of Canada struck down the Criminal Code's prohibition on assisted death. Just over a year later, the federal government crafted legislation to entrench medical assistance in dying (MAiD), the term used in Canada in place of physician-assisted death. Notably, Canada became the first country to allow nurse practitioners to act as assessors and providers, a result of a strong lobby by the Canadian Nurses Association. However, a legislated approach to assisted death has proven challenging in a number of areas. Although it facilitates a degree of accountability, precision and accessibility, it has also resulted in particular challenges negotiating the diverse perspectives of such a morally contentious act. One of these challenges is the tendency to conflate what is legal and what is moral in a modern liberal constitutionalism that places supreme value on autonomy and choice. Such a conflation tends to render invisible the legal and moral/ethical considerations necessary for nurses and nurse practitioners to remain ethical actors. In this paper, we introduce this conflation and then discuss the process of lawmaking in Canada, including the legalization of MAiD and the contributions of nursing to that legalization. We then engage in a hypothetical dialogue about the legal and moral/ethical implications of MAiD for nursing in Canada. We conclude with an appeal for morally sustainable workspaces that, when implementing MAiD, appropriately balance patient choices and nurses’ moral well-being.